Plan de negocios para la creación de una pizzería con productos personalizados en la ciudad de Riobamba - Mesías Aponte, Andrea Nicole (2018)
The business plan detailed in this document aims to determine the commercial and financial viability for the implementation of a pizzeria in the city of Riobamba with the differentiating factor of creating customized products with optimal production times and delivery of the product to the customer, it is structured with necessary information to facilitate decision making by the investor, for which it is essential to take into account the macro and micro environment analysis, customer research through surveys, focus groups and interviews with experts. Within the marketing plan, the strategies to be implemented to reach the target market are determined. In the organizational structure of the project, the necessary personnel is detailed to implement a product development process with time optimization compared to the current existing competition. Finally, the financial analysis seeks to confirm the viability of the project, based on the information acquired during the research process. The analysis of the environments established the existence of a space for the positioning of the business. Competition research determines that the restaurant and pizza industry in the city of Riobamba is highly competitive, since there are low barriers to entry to the market and there is a high rivalry among competitors. The study of the clients establishes that there is a growing market, focused on young people and adults who are looking for a different place to share with family and friends. Based on this information, a financial plan is made in which the initial investment, capital structure, financial statements with a five-year projection and financial comparable indexes are defined with those of the industry in which the project is located. . When carrying out the financial evaluation, the feasibility of the project was determined because the financial indexes that determine the decision making of an investment yield values within the range of positive investment as well as real values that generate profits to the investors.